Avaliação do ciclo de vida da utilização do resíduo do beneficiamento de rochas ornamentais em materiais de construção civil à base de cimento - Mello, Robson Zulcão (2018)
Laboratory technical studies demonstrate the feasibility of using the ornamental stone processing waste (OSPW) for the manufacturing of construction and building materials. However, regarding the environmental aspect, there is still the need to justify its use from an appropriate point of view. Thus, this study presents the life cycle assessment (LCA) of using OSPW for the manufacturing of cement-based building materials, aiming at assessing the OSPW influence on the environmental impact indicators. Altogether, 127 mixtures are analyzed, such as mortars, concretes, masonry and paving blocks. The impacts of OSPW drying and logistics are presented, as well as the burning to produce the heat-treated waste (HTOSPW). The OSPW is as a good alternative to reduce the environmental impact in the Espírito Santo (ES) district, as a replacement for limestone filler, sand or stone dust. It has potential to be used as a cement partial replacement and presented satisfactory results at high replacement levels (over 50%) in the production of rendering and laying mortars and self-compacting concrete. The results also show that the artificial drying alternatives cause a great increase in the OSPW impact, and that its burning produces a pozzolan (HTOSPW) with impact comparable to that of cement CP II-E. Regarding the mixtures production, the cement replacement was the approach most commonly used, causing a reduction in the environment impact indicators of 7.7 to 9.0% for each 10% of OSPW use.